Can Local Institutions Reduce Poverty? Rural Decentralization in Burkina Faso - Donnelly-Roark, Paula; Ouedraogo, Karim; Ye, Xiao (World Bank, Washington, DC, 2014)
The authors present evidence that in Burkina Faso, certain high-performing local institutions contribute to equitable economic development. They link reduced levels of poverty, and inequality to a high degree of internal village organization. The structure of these high-performing local organizations means they can exist in a number of African countries, because they depend more on internal participation, rather than on nay one country's cultural assets. The authors find that: 1) Service-asset management groups (SAMs) - one of three local institutions identified in the study - have helped to significantly reduce inequality in participating households. SAMs are a fusion of long-standing development committees, and indigenous management councils that collectively manage community assets, such as water. SAMs have combined the productivity goals of growth, with the values of equity, and solidarity. 2) Current development approaches use growth as an initiator, assuming that surpluses will be used to benefit the poor. SAMs, and other local institutions in Burkina Faso, start with equity, and solidarity, and aim for a result of growth, and development. 3) Internal participation is essential for SAMs to function. Only locally anchored participation can power the realignments, and institutional revisions needed to scale up development action. SAMs, and other local institutions have launched their communities on equitable growth paths, and are reducing poverty with little, or no outside assistance, despite severe resource constraints. Their impact could be enormous if external development resources augmented their potential. World Bank programs, and policy interventions could build on local strength, and make their activities more sustainable by mapping local institutions to guide new initiatives in pro-poor investment, and using that mapping to formalize, and increase internal local participation - expanding nationwide by using a network of local institutions. SAMs, and other local institutions, could be the vehicle for ensuring transparency, and accountability. Working with the results of local activities, national policies could favor the development of indigenously based, but externally oriented local economies.